Comment: Advances in Studying the Vocal Expression of Emotion: Current Contributions and Further Options. (January 2021) - Scherer, Klaus R.
I consider the five contributions in this special section as evidence that the research area dealing with the vocal expression of emotion is advancing rapidly, both in terms of the number of pertinent empirical studies and with respect to an ever increasing sophistication of methodology. I provide some suggestions on promising areas for future interdisciplinary research, including work on emotion expression in singing and the potential of vocal symptoms of emotional disorder. As to the popular discussion of the respective role of universality versus language/culture differences, I suggest to move on from exclusively studying the accuracy of recognition in judgment studies to a more differentiated approach adding production aspects, taking into account the multiple vocal and acoustic features that interact to communicate emotion.